SOSIALISASI PROGRAM ELEKTRONIK SURAT KUASA UMUM UNTUK MEMBAYAR (E-SKUM) DALAM PENDAFTARAN PERKARA PERDATA DI PEGADILAN NEGERI KELAS IA PEKANBARU - Damai Yanti Simanihuruk; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Counting down payment fee in the registration of civil cases takes longer and convoluted makes Class IA Pekanbaru District Court innovate public service program which is called Elektronik Surat Kuasa Umum untuk Membayar (E-SKUM). The purpose of this program is to make it easier for people who is seeking justice in a civil case registration.This research aims to determine the socialization program Elektronik Surat Kuasa Umum untuk Membayar (E-SKUM) for the registration of civil lawsuits in the District Court of Class IA Pekanbaru and knowing which factors will affect the socialization program Elektronik Surat Kuasa Umum untuk Membayar (E-SKUM) for the registration of civil lawsuits in the District Court of Class IA Pekanbaru. This research uses the concept of socialization theory presented by Laswell. This research uses a qualitative approach with observational data collection techniques, interviews and documentation.Based on the research results through observation and interview, it can be known that the implementation of the socialization program Elektronik Surat Kuasa Umum untuk Membayar (E-SKUM) for the registration of civil lawsuits conducted by the district court of Class IA Pekanbaru has been effective. It is assessed by the achievement of the objectives of the sosialization program E-SKUM. Factors affecting socialization is human resources, public participation and infrastructure.Keywords: Socialization, Elektronik Surat Kuasa Umum untuk Membayar